Influence of APOE polymorphism on cognitive and behavioural outcome in moderate and severe traumatic brain injury. Issue 10 (13th April 2006) - Ariza, M; Pueyo, R; Matarín, M del M; Junqué, C; Mataró, M; Clemente, I; Moral, P; Poca, M A; Garnacho, Á; Sahuquillo, J
Abstract : Aim: To analyse the influence of apolipoprotein (APOE) ε4 status on the cognitive and behavioural functions usually impaired after moderate and severe traumatic brain injury (TBI). Methods: In all, 77 patients with TBI selected from 140 consecutive admissions were genotyped for APOE. Each patient was subjected to neuropsychological and neurobehavioural assessment at least 6 months after injury. Results: Performance of participants carrying the ε4 allele was notably worse on verbal memory (Auditory Verbal Learning Test), motor speed, fine motor coordination, visual scanning, attention and mental flexibility (Grooved Pegboard, Symbol Digit Modalities Test and part B of the Trail Making Test) and showed considerably more neurobehavioural disturbances (Neurobehavioral Rating Scale—Revised) than the group without the ε4 allele. Conclusions: In particular, performance on neuropsychological tasks that are presumed to be related to temporal lobe, frontal lobe and white matter integrity is worse in patients with the APOE ε4 allele than in those without it. More neurobehavioural disturbances are observed in APOE ε4 carriers than in APOE ε2 and ε3 carriers.